The Order of the Poison Oak - Hartinger, Brent (HarperTempest, 2005)
After "coming out" at school, sixteen-year-old Russel decides to take a counselor job at a camp for burn victims to get away from the antagonism of his classmates, but finds ten-year-old boys have just as many problems as he does.